The Regulator of G Protein Signaling Homologous Domain of G Protein-Coupled Receptor Kinase 2 Mediates Short-Term Desensitization of β3-Adrenergic Receptor - Echeverría, Emiliana; Cabrera, Maia; Burghi, Valeria; Sosa, Máximo; Ripoll, Sonia; Yaneff, Agustín; Monczor, Federico; Davio, Carlos; Shayo, Carina; Fernández, Natalia (Frontiers in Pharmacology, 2020)
G protein coupled receptor (GPCR) kinases (GRKs) are key regulators of GPCR signaling. Canonical mechanism of GPCR desensitization involves receptor phosphorylation by GRKs followed by arrestin recruitment and uncoupling from heterotrimeric G protein. Although β3-adrenergic receptor (β3AR) lacks phosphorylation sites by GRKs, agonist treatment proved to induce β3AR desensitization in many cell types. Here we show that GRK2 mediates short-term desensitization of β3AR by a phosphorylation independent mechanism but mediated by its domain homologous to the regulator of G protein signaling (RGS). HEK293T cells overexpressing human β3AR presented a short-term desensitization of cAMP response stimulated by the β3AR agonist, BRL37344, and not by forskolin. We found that β3AR desensitization was higher in cells co-transfected with GRK2. Similarly, overexpression of the RGS homology domain but not kinase domain of GRK2 increased β3AR desensitization. Consistently, stimulation of β3AR increased interaction between GRK2 and Gαs subunit. Furthermore, in rat cardiomyocytes endogenously expressing β3AR, transfection with dominant negative mutant of RH domain of GRK2 (GRK2/D110A) increased cAMP response to BRL37344 and inhibited receptor desensitization. We expect our study to be a starting point for more sophisticated characterization of the consequences of GRK2 mediated desensitization of the β3AR in heart function and disease.